2016
DOI: 10.1021/acs.biochem.6b00572
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Characterization of Patient Derived Mutations Reveal an Unusual Mode of Regulatory Spine Assembly and Drug Sensitivity in EGFR Kinase

Abstract: The catalytic activation of protein kinases requires precise positioning of key conserved catalytic and regulatory motifs in the kinase core. The Regulatory Spine (RS) is one such structural motif that is dynamically assembled upon kinase activation. The RS is also a mutational hotspot in cancers; however, the mechanisms by which cancer mutations impact RS assembly and kinase activity are not fully understood. In this study, through mutational analysis of patient derived mutations in the RS of EGFR kinase, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 77 publications
(180 reference statements)
2
13
0
Order By: Relevance
“…The pEGFP-N1-EGFR plasmid from our previous studies was used for mutagenesis (25,26). The PCR primers for site-directed mutagenesis are designed using the NEBaseChanger v1.2.6 web server from New England Biolabs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pEGFP-N1-EGFR plasmid from our previous studies was used for mutagenesis (25,26). The PCR primers for site-directed mutagenesis are designed using the NEBaseChanger v1.2.6 web server from New England Biolabs.…”
Section: Methodsmentioning
confidence: 99%
“…MD studies on other recurring mutations such as R776H in the αC-β4 loop have identified novel autoinhibitory interactions associated with kinase activation (25) and protonation-dependent changes in mutant EGFR functions (30). In addition, MD-based free-energy methods (26,31), molecular mechanics calculations (32), and molecular modeling studies (33) have provided new insights into mutation-induced drug resistance mechanisms and the conformational transitions connecting active and inactive states (34)(35)(36).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, computational structural modeling and molecular dynamics (MD) simulations have helped us clarify the activation mechanism of EGFR at the atomic level (2527). In addition, predictions of sensitivity of EGFR mutants to EGFR tyrosine kinase inhibitors were performed for several EGFR mutations using binding free energy calculated with MD simulation (28, 29) and fitness scores calculated by molecular docking simulation (30).…”
mentioning
confidence: 99%
“…The procedure for EGFR mutational analysis is described in our previous studies 40 , 41 . Briefly, desired point mutations (S768D, S768E, S768I) were introduced into a pEGFP-N1-EGFR plasmid using QuikChange Site-Directed Mutagenesis Kits (Agilent Genomics, CA, USA).…”
Section: Methodsmentioning
confidence: 99%